Bridging Math Content and Teaching through Pre-Service Undergraduate Apprenticeship - Negrelli, Madeline; Ortiz, Marilyn; Druken, Bridget (Ohio Journal of School Mathematics, 2023)
We describe activities used to learn mathematics teaching during an undergraduate mathematics apprenticeship for preparing single-subject mathematics teaching credential seeking students. During the semester-long experience set in an undergraduate mathematics course for future elementary teachers, two apprentices and one university faculty attended weekly class sessions and meetings to deepen their knowledge for teaching mathematics. Six activities for supporting teacher training apprenticeships are shared and exemplified.